Aedes Sp. Larvae Density Related to DHF Incidence in Tamalate District of Makassar City - Paizah, Nurrahmi; Susilawaty, Andi; Surahmawati, Surahmawati; Basri, Syahrul (HIGIENE: Jurnal Kesehatan Lingkungan, 2021)
Dengue Hemorrhagic Fever (DHF) is a disease that is transmitted by the Aedes sp. In 2019 there were 138,127 cases with 919 deaths. One of the factors that influence the increase or decrease in the incidence of Dengue Hemorrhagic Fever (DHF) is the population of Aedes aegypti mosquito larvae. The purpose of this study was to measure the density of Aedes sp. related to the incidence of DHF in Tamalate District, Makassar City. This research is a descriptive type of research, with a visual survey method. The research sample is the number of cases in 2017 which is as many as 20 samples with the inclusion criteria of mosquito flight distance to meet the number of 100 samples. The results of the study of 100 houses inspected in Tamalate District there were 28 houses that were positive for larvae, thus obtaining a House Index (HI) value of 28%, and included in the medium density category, from 524 containers inspected in Tamalate District there were 44 positive containers. larvae were found, thus obtaining a Container Index (CI) value of 8.3%, included in the medium density category, there were 44 positive larval container containers from 100 houses inspected in Tamalate District, thus obtaining a Breteau Index (BI) value of 44% and included in the category medium density level, for the Density Figure category the House Index (HI) value of 28 so that the results of Density Figure (DF) 4 are included in the Density Figure (DF) category of medium density, the result of Container Index (CI) 8.3 so that the results of Density Figure ( DF) 3 is included in the Density Figure (DF) category of medium density, and the results of the Breteau Index (BI) 44 so that m get the results Density Figure (DF) 5 is included in the Density Figure (DF) category of medium density. Researchers suggest to the public to carry out PSN activities continuously with the 3M Plus method.